Human induced pluripotent stem cell line (QBRIi013-A) derivation from a 6-year-old female diagnosed with Autism spectrum disorder (ASD) and intellectual disability (ID) - Ahmed K. Elsayed (13275302) (2021)
Autism spectrum disorder (ASD) is a childhood-onset neurodevelopmental disorder characterized by social interaction, behavior, and communication challenges. Here, we generated an induced pluripotent stem cell (iPSC) line, QBRIi013-A using a non-integrating Sendai virus from a 6-year-old female diagnosed with ASD and intellectual disability. The QBRIi013-A cell line was fully characterized and exhibited a pluripotency capacity and trilineage differentiation potential. Furthermore, it showed normal karyotype and genetic identity to the patient’s PBMCs. Consequently, this iPSC line provides a valuable cell model in understanding the molecular mechanism underlying the complexities of ASD pathogenesis. Other Information Published in: Stem Cell Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.scr.2021.102500